Pembuatan kulit tahan air untuk bagian atas sepatu - Wiryodiningrat, Suliestiyah (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2008)
Â Â Â Â Â Â Â The aim of research non manufacturing of waterproof leather for shoe upper is to find the best formula in producing waterproof cow hide leather for shoe uppers. Today, the tanners trying their best effort to fulfill the shoes. The research used salted raw cow hide 18 sides were utilized. Leather treatment process begining with soaking stage up to tanning stage and using the same formula in each treatment. In the fatliquoring stage, the treatment varied in the number of fatliquoring chemical material were 8,10, and 12 % respectively. Whereas, the amount of was silicon added in the dyeing process were 5,7.5, and 10 % respectively. The quality of the leather was physically examined accordance with testing method of ISO. 8782- 1998 â¬ and DIN standard. The results performed that the best formula was sample with addition of fatliquoring 12 % and silicon5%.Â Key words : fatliquoring, silicon, waterproof leatherÂ ABSTRAKÂ Â Â Â Â Â Â Â Â Â Â Tujuan penelitian adalah mencari formula terbaik untuk mengahsilkan kulit waterproof dari kulit sapi sebagai bahan bagian atas sepatu (shoe uppers). Saat ini para pengusaha penyamakan kulit berusaha memenuhi kulit waterproof yang sangat diperlukan oleh para pengusaha sepatu khususnya untuk sepatu olahraga. Kulit sapi mentah awet garam sebanyak 9 lembar digunakan dalam penelitian. Proses pengolahan kulit dimulai dari tahap perendaman sampai tahap penyamakan, menggunakan formula yang sama untuk setiap perlakuan. Proses pengemukakan /perminyakan, digunakan variasi jumlah fatliquoring sebanyak berturut-turut : 8,10, dan 12 %. Sedangkan jumlah silicon yang ditambahkan pada proses pengecatan sebanyak berturut-turut : 5,7.5 da 10 %. Hasil penelitian, diuji secara fisis berdasarkan 1S0. 8782-1998 (E) dan DIN Standar. Formula terbaik dihasilkan oleh formula dengan variasi penggunaan fatliquoring sebanyak 12 % dan silicon sebanyak 5%.Â Kata Kunci : fatliquoring, silicon, kulit waterproof.